2021
DOI: 10.3390/ma14092337
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Properties of Synthetic Polypropylene Fiber–Reinforced Renewable Oil Palm Shell Lightweight Concrete

Abstract: Oil palm shell (OPS) is an agricultural solid waste from the extraction process of palm oil. All these wastes from industry pose serious disposal issues for the environment. This research aims to promote the replacement of conventional coarse aggregates with eco-friendly OPS aggregate which offers several advantages, such as being lightweight, renewable, and domestically available. This paper evaluates the mechanical and thermal performances of renewable OPS lightweight concrete (LWC) reinforced with various t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This is particularly correct where fibre prolongs concrete's ability to sustain the load and withstand large deformation without fracturing into pieces. Similar behaviour has been reported for PP and PVC fibre OPS lightweight concrete Yew et al, 2016;Loh et al, 2021). The failure pattern of CLLWAC-BPP0% and CLLWAC-BPP0.45%, as shown in Figure 6.…”
Section: 4splitting Tensile Strengthsupporting
confidence: 80%
“…This is particularly correct where fibre prolongs concrete's ability to sustain the load and withstand large deformation without fracturing into pieces. Similar behaviour has been reported for PP and PVC fibre OPS lightweight concrete Yew et al, 2016;Loh et al, 2021). The failure pattern of CLLWAC-BPP0% and CLLWAC-BPP0.45%, as shown in Figure 6.…”
Section: 4splitting Tensile Strengthsupporting
confidence: 80%
“…Based on the result from figure 2, it can be observed that the compressive strength decreases when the OPS and w/c ratio increase. An inversely proportional relationship is found between slump diameter and compressive strength, which can be explained that OPS absorbed the water from the mortar due to the porous structure [3]. LWFC-CTR can resist higher compressive force compared to LWFC-OPS5.…”
Section: Compressive Strengthmentioning
confidence: 87%
“…In this study, Orang Kuat Type I Ordinary Portland Cement was used in this study, which is in accordance with the standard of ASTM: C150/C150M-12. The specific gravity for this cement was 3.14 g/cm 3 . Local fine sand was used and passing through the 600µm of sieve.…”
Section: Materials and Me Thodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, lightweight foamed concrete is produced by adding foaming agent in which up to 75% of air-voids can be entrapped in mortar mix. According to Loh et al, one of the most popular techniques to produce lightweight concrete is to incorporate lightweight aggregate [34]. From the previous study, high strength lightweight concrete incorporated plant-based aggregate is generally obtained a compressive strength within the range of 40-54 MPa and oven-dry density less than 1900 kg/m 3 [26].…”
mentioning
confidence: 99%